#TITLE_ALTERNATIVE# - NUGRAHA (NIM 20305003), RUKMAN
The determination of primordial perturbations is a key to understand physicals information of early universe. In this way, CMB anisotropies and its polarizations can be used as media and cosmic inversion as method. In this work, we develop mathematical construction of cosmic inversion for tensor perturbations. In doing the construction two approximations are used, the thickness of last scattering surface is thin and small angle approximation. Because of the first approximation, within recombination, projection factor is constant and transfer function is time-integrated. Unfortunately, this makes a multipol moment approximation for CMB anisotropies is deviate from exact calculation. In the other hand, a multipol moment approximation for E-type and B-type of CMB polarization are close with exact calculation. By using small angle approximation, cosmic variance effect can be avoided. Beside that, mathematical construction for B-type of CMB polarization is simpler. Consequently, we can find a value for reconstructed primordial tensor perturbation power spectrum even at zero point of its transfer function, which suppose to oscillate. Final effect of utilization of those two approximations is a reconstructed power spectrum of primordial tensor perturbation would be incorrect. To remedy this effect, an iterative method, which used for scalar perturbation, can be used. By using this technique, a correct value of reconstructed power spectrum of primordial tensor perturbation would be obtained.